Lost in translation: Decoding the errors in consecutive interpreting by Chinese EFL learners - Yajin Zhuang; Liwen Chen (PLoS ONE, 2025)
Errors, as linguistic manifestations of cognitive challenges in interpreting, have attracted considerable attention in the fields of teaching, practice, and assessment. This paper examines the nature of interpreting errors among Chinese EFL (English as a Foreign Language) learners and explores their relationship with gender differences and interpreting performance, using the parallel corpus of Chinese EFL Learners-Spoken (PACCEL-S). The findings indicate the following: (1) improper speech flow was the most frequent and dense type of error, followed by grammatical errors and semantic deviations, while information default occurred least frequently. These patterns can be attributed to deficiencies in learners’ language proficiency, interpreting skills, and emotional regulation; (2) only grammatical errors showed a statistically significant correlation with gender, suggesting that gender-related differences in communication psychology may influence interpreting performance; (3) semantic deviation, information default, and improper speech flow were all significantly and negatively correlated with interpretation scores, whereas grammatical errors showed no significant correlation with these scores. These results suggest that English proficiency assessments may tolerate a certain degree of grammatical errors in interpreting tasks. Situated within the context of interpreting education, this study extends research on interpreting errors, enriches interpreting pedagogy and assessment, and deepens our understanding of the challenges faced by Chinese EFL learners.